2018
DOI: 10.1177/016146811812001305
|View full text |Cite
|
Sign up to set email alerts
|

Locating Black Girls in Educational Policy Discourse: Implications for the Every Student Succeeds Act

Abstract: The enactment of the Every Student Succeeds Act (ESSA) in 2015 by President Barack Obama increased accountability requirements and was designed to reduce achievement and opportunity gaps, and racial disproportionality in school discipline. Despite the implementation of ESSA, Black girls still continue to experience hypercriminalization and policing, and when disaggregated by race and gender, they still receive the highest rates of disciplinary punishments in school and out of school. In this article, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Rather, our analysis suggests that school policies and practices shaping negative outcomes for Black girls must also be unpacked at the interpersonal level to fully understand the dynamic nature of power. This is key because teachers and school leaders play a critical role making sense of how policies and practices are perceived and how they are implemented in schools (Braun et al, 2011; Evans-Winters et al, 2018). However, few studies illustrate ways educators grapple with these microlevel practices and how they come to understand policies through the lens of their values and preexisting beliefs and ideologies about Black girls and their identities.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our analysis suggests that school policies and practices shaping negative outcomes for Black girls must also be unpacked at the interpersonal level to fully understand the dynamic nature of power. This is key because teachers and school leaders play a critical role making sense of how policies and practices are perceived and how they are implemented in schools (Braun et al, 2011; Evans-Winters et al, 2018). However, few studies illustrate ways educators grapple with these microlevel practices and how they come to understand policies through the lens of their values and preexisting beliefs and ideologies about Black girls and their identities.…”
Section: Discussionmentioning
confidence: 99%
“…While the most voluminous research on genderspecific student violence has focused on school staffs' interactions with Black boys (Andrews, 2015;Basile et al, 2020Basile et al, , 2022Bryan, 2020;Caton, 2012;Collins et al, 2023;Henfield, 2011;Howard, 2014;Noguera, 2009;Patton et al, 2012;Payne & Brown, 2010;Webster & Knaus, 2021), there is growing body of work on school staffs' interactions with Black girls (Aldridge, 2018;B. N. Anderson, 2020;Butler-Barnes & Inniss-Thompson, 2020;Crenshaw et al, 2015;Epstein et al, 2017;Evans-Winters, 2005;Evans-Winters & Hines, 2022;Hines-Datiri & Carter Andrews, 2020;Wun, 2016). One teen dating violence study conducted with middle schoolers found that Black girls were more likely than White girls to perpetrate threatening behaviors, verbal/emotional abuse, and physical violence (Niolon et al, 2015).…”
Section: Review Of Relevant Literature Gendered Dimensions Of Violencementioning
confidence: 99%
“…Black women and girls are missing not only from Brown but also from larger conversations regarding equitable education because scholars, educators, policymakers, and broader society are not socialized to see them as powerful actors. Intersectionality teaches us that Black women and girls simply are not palatable, making it easy for them to go unnoticed despite being in plain sight (Collins 2017;Crenshaw et al, 2015;Evans-Winters et al, 2018;J. Harris & Kruger, 2023; J. C. Harris & Patton, 2019;Patton & Haynes, 2018;Steele, 2022).…”
Section: Counternarrative 2: Black Girls and Women Shaped The Movementmentioning
confidence: 99%